Experimental investigation on thermo-physical properties of metal oxide composite nanolubricants - N. M. M., Zawawi; Azmi, W. H.; A. A. M., Redhwan; M. Z., Sharif; Mahendran, Samykano (Elsevier, 2018)
The thermal conductivity and dynamic viscosity of three different combinations of metal oxide composite nanolubricant had been investigated at different nanoparticle volume concentrations (0.02 to 0.1%) and different temperatures (303–353 K). The prepared Al2O3–SiO2, Al2O3–TiO2 and TiO2–SiO2 composite metal oxide nanoparticle was dispersed in Polyalkylene Glycol (PAG 46) lubricant by espousing the two-step preparation method. The thermal and viscosity experiment was performed using KD2 Pro Thermal Properties Analyzer and LVDV-III Rheometer, respectively. All the considered metal oxide composite nanolubricants were witnessed to behave as Newtonian fluids. A maximum viscosity enhancement of 20.50% recorded for Al2O3–TiO2/PAG nanolubricant with 0.1% nanoparticle volume concentration and at the temperature of 303 K. Whereas, the highest thermal conductivity improvement recorded for Al2O3–SiO2/PAG nanolubricant with 2.41% improvement at 0.1% nanoparticle concentration and temperature of 303 K. A new regression model to estimate the dynamic viscosity and thermal conductivity of metal oxide composite nanolubricants were proposed based on the finding obtained.